Suitability of using symmetric key to secure multimedia data: an overview, - Abomhara, Mohamed; Khalifa, Othman Omran; Zakaria, Omar; Zaidan, A. A.; Zaidan, B. B.; Alanazi, Hamdan O. (Asian Network for Scientific Information, 2010)
With the increasing and continuous use of digital communications on the internet in recent times, security is becoming more and more relevant and important. However, special and reliable security is required for the many digital applications available such as video conferencing, digital television and mobile TV. The classical techniques of data security are not appropriate for the current multimedia usage. This study addresses the current algorithm of multimedia encryption schemes that have been proposed in the literature and description of multimedia security. It is a comparative study between symmetric key encryption and asymmetric key encryption in achieving an efficient, flexible and secure video data